Hajj Economy: A Bibliometric Analysis - Antonio, Muhammad Syafii (Halal Tourism and Pilgrimage, 2025)
This study aims to map the development and direction of global research related to Hajj Economic through a bibliometric approach and meta-analysis of Scopus indexed scientific publications. The research data consisted of 137 journal articles relevant to the topic of Hajj economics, analyzed using VOSviewer software to identify collaboration patterns, dominant keywords, and thematic clusters of research. A descriptive qualitative approach is used to interpret the intellectual structure and dynamics of research based on keyword mapping and co-citation. The results of the analysis revealed five main clusters, namely: (1) Sustainable Hajj Economics and Geopolitics, (2) The Economic Impact on the Health of Hajj Pilgrims, (3) Hajj Risk Economic Management, (4) Indonesian Hajj Economy, and (5) Hajj Economic Decision Making. The findings show that the hajj economy functions not only as a worship activity, but also as a complex economic system involving public health issues, risk management, geopolitics, Islamic financial governance, and Islamic value-based decision-making. This research contributes by providing a comprehensive map of the Hajj Economic literature and identifying relevant future research opportunities for policymakers and academics.